2017
DOI: 10.2147/dddt.s114932
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on ertugliflozin and its potential in the treatment of type 2 diabetes: evidence to date

Abstract: Sodium-glucose cotransporter 2 (SGLT2) inhibitors are the latest therapeutic strategy in the treatment of type 2 diabetes mellitus (T2DM). Using an insulin-independent mechanism (glycosuria), they reduce glucose toxicity and improve insulin sensitivity and β-cell function. The promising results obtained in clinical trials show that SGLT2 significantly improves glycemic control and provides greater cardiovascular protection, combined with a reduction in body weight and blood pressure (BP). This review focuses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 59 publications
0
56
0
5
Order By: Relevance
“…The efficacy of combination therapy with ertugliflozin and sitagliptin observed in this study is consistent with that observed in other studies in the VERTIS program [ 18 , 19 ]. In the VERTIS FACTORIAL study, adding the combination of ertugliflozin (5 or 15 mg) and sitagliptin to the treatment of patients on metformin reduced HbA1c by 1.5% from a baseline of 8.6% (70 mmol/mol), which was superior to the effect of either agent alone [ 19 , 20 ]. In the present study, patients were not receiving background AHAs, and the mean baseline HbA1c of 8.9% was slightly higher than that in VERTIS FACTORIAL; the observed LS mean reductions from baseline in HbA1c for the E5/S100 and E15/S100 groups were slightly larger than those observed in the VERTIS FACTORIAL study (1.5% for both combination therapy groups).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of combination therapy with ertugliflozin and sitagliptin observed in this study is consistent with that observed in other studies in the VERTIS program [ 18 , 19 ]. In the VERTIS FACTORIAL study, adding the combination of ertugliflozin (5 or 15 mg) and sitagliptin to the treatment of patients on metformin reduced HbA1c by 1.5% from a baseline of 8.6% (70 mmol/mol), which was superior to the effect of either agent alone [ 19 , 20 ]. In the present study, patients were not receiving background AHAs, and the mean baseline HbA1c of 8.9% was slightly higher than that in VERTIS FACTORIAL; the observed LS mean reductions from baseline in HbA1c for the E5/S100 and E15/S100 groups were slightly larger than those observed in the VERTIS FACTORIAL study (1.5% for both combination therapy groups).…”
Section: Discussionmentioning
confidence: 99%
“…In previous clinical studies, ertugliflozin used as a monotherapy [ 16 ], as an add on to metformin [ 17 ], as an add on to the combination of sitagliptin and metformin [ 18 ], and in combination with sitagliptin as an add on to metformin [ 19 , 20 ] improved glycemic control, reduced body weight, and generally reduced blood pressure with a low incidence of hypoglycemia. In other studies, sitagliptin used as a monotherapy [ 21 ] or as part of a dual therapy with metformin [ 22 ] also provided clinically meaningful reductions in blood glucose with a low risk of hypoglycemia or weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…The VERTIS CV trial will assess CV safety and efficacy of ertugliflozin in patients at high CV risk and will report in about 1 year. Adverse effect information is available from the product monograph (http://www.merck.ca/static/pdf/STEGLATRO-PM_E.pdf) and from a meta‐analysis of available phase 2/3 efficacy and safety data . Currently the risk profile appears to be similar to that observed with empagliflozin and dapagliflozin although a small increased risk of amputation has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ertugliflozin is chemically (C22H25ClO7): 2 The molecular structure of Ertugliflozin is depicted in Figure 1. 2…”
Section: Chemical Structure Of Ertugliflozinmentioning
confidence: 99%